REPRESENTASI NILAI AGAMA DALAM IKLAN BILLBOARD RABBANI (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) (The Commercium, 2023)
An advertisement is an attractive message that has the purpose of persuading someone to buy a product or service. In order to attract the attention of potential buyers, the Rabbani brand makes advertisements that are quite controversial in the community, while Rabbani itself always carries religious values in each of their advertisements. This research aims to find out the representation of religious values from Rabbani's billboard advertisements, especially the headscarf advertisements for school children. For this reason, this research uses a descriptive qualitative approach. The method of data collection is by collecting all elements of the advertisement and analyzing them using Charles Sanders Peirce's triangle of meaning theory. Based on the results of the analysis, the representation of religious values from Rabbani billboard advertisements illustrates the value of adab in laughing and the value of sharia, namely the obligation to cover the veil with a headscarf for women.